ANALISIS PERBANDINGAN KEPUASAN KONSUMEN DITINJAU DARI KUALITAS PRODUK PADA OBJEK WISATA AIR TERJUN PARANG IJO DENGAN WISATA AIR TERJUN JUMOG DI KABUPATEN KARANGANYAR - Onesta Sukarno Putro, Sumaryanto & Retno Susanti (Universitas Slamet Riyadi, 2016)
The purpose of this research was: 1) to analyze the significance of the difference of consumer satisfaction in terms of product quality in sights of waterfalls Parang Ijo with Jumog waterfall sights in Karanganyar Regency. 2) to analyze the significance of the difference of consumer satisfaction in the sights of waterfalls Parang Ijo with Jumog waterfall sights in Karanganyar Regency. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of secondary. The population in this research is the consumer visitors have enjoyed the sights of waterfalls Parang Ijo with Jumog waterfall sights in Karanganyar Regency. As for the number of samples used in the study was as much as 100 respondents to attractions waterfalls Parang Ijo and as many as 100 respondents to Jumog waterfall tourist attraction. Methods of data collection were used: questionnaire, documentation. Technique of data analysis used the test of validity, reliability test, test of normality and Independent Sample T-Test results obtained. conclusion: 1) there is a significant difference in terms of consumer satisfaction product quality on attractions waterfalls Parang Ijo with Jumog waterfall sights in Karanganyar Regency. 2) there is a significant difference in consumer satisfaction attractions waterfalls Parang Ijo with Jumog waterfall sights in Karanganyar Regency.Keywords: customer satisfaction, product quality, attractions waterfalls